The Relationship of Social Support with Academic Achievement and Career Aspiration of Grade- 8 Students in Myanmar - Thwet Thiri Soe (Technium Social Sciences Journal, 2020)
A major concern for educational institutions is improving the quality of lives of students. This study investigated the relationship between social support and academic achievement of students and career aspiration of students in Myanmar. The quantitative research methodology, (survey method) was applied and 550 Grade- 8 students from public schools within Yenanchaung Township, Myanmar. Students in this study completed the two questionnaires, the social support questionnaore and the social support for career aspiration questionnaire to assess their received social support from their parents, teachers and peers. The researcher developed these questionnaires based on the four types of social support by Tardy (1985). The results of the data analysis suggest that there is a positive relationship between social support and academic achievement and the social support and students’ career aspiration.